2005
DOI: 10.1177/112067210501500617
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, Vitamin B12, and Folic Acid in Age-Related Macular Degeneration

Abstract: Hyperhomocysteinemia might be one of the risk factors for the exudative form of ARMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…These findings indicate an association of markers of angiogenesis, hemostasis, and endothelial dysfunction with AMD. This hypothesis is supported by the results of the study by Nowak et al (2005a), which reported an association between AMD and atherosclerosis. High levels of homocysteine result in direct vascular endothelial injury by releasing free radicals, inhibiting glutathione peroxidase and nitric oxide, interfering with clotting factors and lipid peroxidation, all of which modify the vessel wall (Genser et al 2006;Papandreou et al 2006).…”
supporting
confidence: 81%
“…These findings indicate an association of markers of angiogenesis, hemostasis, and endothelial dysfunction with AMD. This hypothesis is supported by the results of the study by Nowak et al (2005a), which reported an association between AMD and atherosclerosis. High levels of homocysteine result in direct vascular endothelial injury by releasing free radicals, inhibiting glutathione peroxidase and nitric oxide, interfering with clotting factors and lipid peroxidation, all of which modify the vessel wall (Genser et al 2006;Papandreou et al 2006).…”
supporting
confidence: 81%
“…Homocysteine has been suggested as a biomarker of cardiovascular disease (Boushey et al, 1995). Additionally, studies not only found that homocysteine was significantly elevated in AMD patients (Kamburoglu et al, 2006; Rochtchina et al, 2007; Vine et al, 2005) but that the levels were higher in nvAMD vs. the dry form of AMD (Coral et al, 2006; Ghosh et al, 2013; Nowak et al, 2005). Although these data may support using serum homocysteine levels as a surrogate marker and screening for AMD, the studies had small numbers of cohorts yielding low statistical power.…”
Section: Biomarkers Of Disease and Progressionmentioning
confidence: 99%
“…Recent cross-sectional (1719) and case-control (2024) studies indicate a direct association between homocysteine concentration in the blood and risk of AMD, suggesting that homocysteine may be a modifiable risk factor for AMD. Homocysteine is an intermediary amino acid formed during the metabolism of methionine, an essential amino acid derived from protein (25).…”
Section: Introductionmentioning
confidence: 99%